Tracing the Evolution of Community Empowerment Models in Development Planning - Mustanir, Ahmad; Sellang, Kamaruddin; Adnan, A. Astinah; Lubis, Sandi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study examines community empowerment models in development planning to identify the most effective and relevant across various socio-political contexts. It examines central themes, research trends, and challenges in community empowerment through a systematic literature review and bibliometric analysis. The article search was conducted comprehensively using the Scopus database, focusing on publications from 2014 to 2024 to ensure a focus on the most recent developments in the field. The results indicate that the Asset-Based Community Development (ABCD), Participatory Rural Appraisal (PRA), and Community-Led Development (CLD) models are the most effective approaches for empowering communities when supported by robust institutional frameworks and adapted to local contexts. This study also highlights the importance of institutional support and a deep understanding of external power structures in enhancing the resilience and sustainability of community empowerment initiatives. These findings suggest the need for further exploration of the interactions between these empowerment models and external factors, such as economic pressures and social hierarchies, to develop more adaptive and contextually appropriate strategies. Further research is also needed on the scalability and long- term sustainability of these models, particularly in diverse and evolving development settings, to ensure that community empowerment efforts can effectively address the complexities of modern development challenges.